Make the cut : a communication campaign that promotes using fashion to combat textile waste - Cheo, Peijun (2017)
Make The Cut is the first communication campaign in Singapore that addresses the issue of textile waste using a fashion-centric framework. It aims to educate and motivate Singaporean females age 18 to 25 to maximise the use of clothes through green consumerism activities — restyling and repurposing clothes — to combat textile waste. The campaign was developed and implemented by four final year undergraduates from the Wee Kim Wee School of Communication and Information at Nanyang Technological University, Singapore. Although Singapore has experienced an increase in textile waste output by 61% since 2008, textile waste recycling rates remain stagnant at 7% as of 2016. The team’s preliminary research found that Fast Fashion contributes largely to the increasing rate of textile waste accumulation. Past campaigns in Singapore and overseas promoted technical and tedious skills, which challenged the audience from adopting green consumerism in the long run. Drawing on these findings, the team developed a strategic communication plan that engaged the audience in maximising the use of clothes to combat textile waste. Restyling and repurposing of clothes were promoted through social media and hands-on activities. The campaign saw success with overall increase in improving attitudes and behavioural intention to restyle and repurpose among the target audience. Through process evaluations of various campaign phases, the team successfully increased the target audience’s understanding of restyling and repurposing as sustainable lifestyle choices. This campaign opens the door to future possibilities of the adoption of environmentally-friendly lifestyle habits, through a fashion-centric approach to combat textile waste.